Should research ethics committees be told how to think?. Issue 1 (5th January 2007) - Sayers, G M
Abstract : Research ethics committees (RECs) are charged with providing an opinion on whether research proposals are ethical. These committees are overseen by a central office that acts for the Department of Health and hence the State. An advisory group has recently reported back to the Department of Health, recommending that it should deal with (excessive) inconsistency in the decisions made by different RECs. This article questions the desirability and feasibility of questing for consistent ethical decisions.